2022
DOI: 10.3389/fcvm.2021.824128
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Multiple Intravascular Imaging Techniques in Acute Coronary Syndrome

Abstract: Recent advances in intravascular imaging techniques have made it possible to assess the culprit lesions of acute coronary syndrome (ACS) in the clinical setting. Intravascular ultrasound (IVUS) is the most commonly used intravascular imaging technique that provides cross-sectional images of coronary arteries. IVUS can assess plaque burden and vessel remodeling. Optical coherence tomography (OCT) is a high-resolution (10 μm) intravascular imaging technique that uses near-infrared light. OCT can identify key fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Another study comparing 40 MHz IVUS and OCT in patients with ACS showed a 40 and 73% incidence of PR identified by IVUS and OCT, respectively [ 34 ]. Conventional IVUS cannot determine the presence or absence of small ruptures owing to its coarse resolution; hence why this technique poorly identifies PE [ 35 ]. However, in patients with ascertained PE, OCT can be visualized using HD-IVUS [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study comparing 40 MHz IVUS and OCT in patients with ACS showed a 40 and 73% incidence of PR identified by IVUS and OCT, respectively [ 34 ]. Conventional IVUS cannot determine the presence or absence of small ruptures owing to its coarse resolution; hence why this technique poorly identifies PE [ 35 ]. However, in patients with ascertained PE, OCT can be visualized using HD-IVUS [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…IVUS has been the cornerstone of intracoronary imaging for 20 years and can provide information on plaque burden and remodeling. In contrast, OCT has advantages in detecting fibrous cap thickness and thrombus formation [ 4 ]. However, OCT has several limitations, such as the need for complete blood removal and the use of contrast agents, even in patients with chronic kidney disease; this sometimes precludes the assessment of the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…NIRS can detect lipid composition by analyzing the near-infrared absorption properties of atherosclerotic plaques. A thorough discussion of hybrid intravascular imaging modalities can be found in Bourantas et al (2017) and Kubo et al (2022) .…”
Section: Pipeline Of Image-based Computational Biomechanical Simulationsmentioning
confidence: 99%
“…A detector at the tip of the catheter collects ultrasound echoes or backscattered light signals. Finally, sequential cross-sectional images (short-axis view or B mode) that show cross sections of the vessels, including lumen, adventitia/media, intima, and plaque load [2] are formed. Longitudinal view (L-view) slices along the long axis of the vessel segment (i.e., time-axis view) are also obtained for volumetric analysis.…”
Section: Introductionmentioning
confidence: 99%